Synergistic Effects of Problem-Based Learning and VAK Learning Styles on Critical Thinking and Self-Efficacy in High School Chemistry - Sugrah, Nurfatimah; Mustafa, Linda Kurnia; Rakhman, Khusna Arif; Ahmar, Dewi Satria; Rahim, Fazly; Inayah, Nurul (Jurnal Pendidikan MIPA, 2025)
This study investigated the impact of learning styles and learning models on students’ critical thinking skills and self-efficacy in chemistry, with a focus on atomic structure and fundamental chemical laws. The research design employed was a quasi-experimental 2×3 factorial design with 108 tenth-grade high school students. The independent variables were the learning model (Problem-Based Learning/PBL and direct instruction) and learning styles (visual, auditory, kinesthetic). In contrast, the dependent variables were critical thinking skills and self-efficacy. Data were collected using the VAK learning style inventory, a validated critical thinking test, and a self-efficacy questionnaire. Data analysis employed two-way ANOVA followed by Tukey HSD post hoc tests. The results revealed that both learning models and learning styles significantly impacted students’ critical thinking skills. Students with kinesthetic learning styles performed better in critical thinking than those with visual or auditory learning styles. However, learning styles did not significantly influence self-efficacy, suggesting that students’ confidence is more strongly shaped by mastery experiences, positive feedback, and social support. The PBL model significantly enhanced both critical thinking skills and self-efficacy, highlighting the value of collaborative and contextual learning activities in developing higher-order thinking and motivation. A significant interaction was observed between learning styles and learning models, with a notable benefit for visual and kinesthetic learners in terms of self-efficacy. This study acknowledges the fundamental limitation of the VAK framework, as empirical evidence for its validity remains weak; hence, interpretations should be made cautiously. Theoretically, the findings support Bandura’s social cognitive theory, which emphasizes that self-efficacy and learning outcomes are shaped through active engagement and authentic experiences. Practically, this study suggests designing adaptive PBL approaches aligned with learners’ diverse characteristics to optimize both motivation and confidence in chemistry learning. Keywords: learning styles, problem-based learning (PBL), critical thinking skills, self-efficacy.